Terrain-surface Estimation from Body Configurations of Passive Linkages. (6th February 2014) - Chugo, Daisuke; Kawabata, Kuniaki; Kaetsu, Hayato; Asama, Hajime; Mishima, Taketoshi
A passive linkage mechanism is used for increasing the mobile performance of a wheeled vehicle on uneven ground. The mechanism changes its shape according to the terrain and enables all the wheels to remain grounded while the vehicle operates over rough terrain. This means that the shape of the passive linkage mechanism must correspond to that of the terrain surface, so that the vehicle can estimate the shape of the surface while passing over it. This paper proposes a new terrain-surface estimation scheme that uses a passive linkage mechanism. Our key concept is to enable changes in the vehicle body's configuration to correspond to those in the terrain's shape. Using this concept, our mobile platform estimates the shape of terrain surfaces without using external sensors; the estimated surface shapes are used to adjust the reference velocities of individual wheels, thereby improving the mobile performance of the vehicle. We test our proposed scheme by experiments using a prototype vehicle.